Implementation Of Inclusive Education Policy At The High School/Vocational School (State) Level In Jombang Regency - Nugroho Hadi Ichda Saputra; Dian Ferriswara; Ulul Albab; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze comprehensively and in detail about: Implementation of Inclusive Education at the High School/Vocational School (State) Level in Jombang Regency and factors that affect the Implementation of Inclusive Education at the High School/Vocational School (State) Level in Jombang Regency. This research is a qualitative research, with data collection techniques using interviews, observations, and documentation. Data analysis techniques Interactive data analysis. The results of the study show that the Implementation of Inclusive Education at the High School/Vocational School (State) Level in Jombang Regency is carried out in several stages, namely inclusive education planning, inclusive education organization, inclusive education management, and inclusion education evaluation. Factors Affecting the Implementation of Inclusive Education at the High School/Vocational (State) level in Jombang Regency include: The first factor is the Communication Aspect which is carried out by means of socialization of the Inclusion education policy carried out by the Jombang Regency Education Office to school principals, staff, committees and teachers, the second factor is the Resource Aspect that is supported 715 staff including educators and non-educators who are ready to support the Inclusive Education Policy, the Third Factor of the Commitment Aspects, the Jombang Regency Education Office makes a policy that All High Schools/Vocational Schools in Jombang are Required to Accept Students with Mild Disabilities, the Fourth Factor of the Bureaucratic Structure which is marked by the existence of The Jombang Regency Education Office has coordinated with Supervisors, Principals and Teachers in implementing the Inclusion education policy.